Responding to globalization : a decent work agenda for the Caribbean in the context of regional integration (ILO Port of SpainTT, 2006)
Debates and demonstrates how the decent work approach, based largely as it is on the appropriate implementation of ILO Conventions, together with efforts to find a job-creating macro- and micro-economic framework, can advance the development agenda in a globalising world.
Keywords: EMPLOYMENT POLICY